A Strigolactone Signal Inhibits Secondary Lateral Root Development in Rice - Sun, Huwei; Xu, Fugui; Guo, Xiaoli; Wu, Daxia; Zhang, Xuhong; Lou, Manman; Luo, Feifei; Zhao, Quanzhi; Xu, Guohua; Zhang, Yali (Frontiers in Plant Science, 2019)
Strigolactones (SLs) and their derivatives are plant hormones that have recently been identified as regulators of primary lateral root (LR) development. However, whether SLs mediate secondary LR production in rice (Oryza sativa L.), and how SLs and auxin interact in this process, remain unclear. In this study, the SL-deficient (dwarf10) and SL-insensitive (dwarf3) rice mutants and lines overexpressing OsPIN2 (OE) were used to investigate secondary LR development. The effects of exogenous GR24 (a synthetic SL analogue), 1-naphthylacetic acid (NAA; an exogenous auxin), 1-naphthylphthalamic acid (NPA; a polar auxin transport inhibitor) and abamine (a synthetic SL inhibitor) on rice secondary LR development were investigated. Rice d mutants with impaired SL biosynthesis and signalling exhibited increased secondary LR production compared with wild-type (WT) plants. Application of GR24 decreased the numbers of secondary LRs in dwarf10 (d10) plants but not in dwarf3 (d3), plants. These results indicate that SLs negatively regulate rice secondary LR production. Higher expression of DR5::GUS and more secondary LR primordia were found in the d mutants than in the WT plants. Exogenous NAA application increased expression of DR5::GUS in the WT, but had no effect on secondary LR formation. No secondary LRs were recorded in the OE lines, although DR5::GUS levels were higher than in the WT plants. However, on application of NPA, the numbers of secondary LRs were reduced in d10 and d3 mutants. Application of NAA increased the number of secondary LRs in the d mutants. GR24 eliminated the effect of NAA on secondary LR development in the d10 mutants, but not in the d3, mutants. These results demonstrate the importance of auxin in secondary LR formation, and that this process is inhibited by SLs via the D3 response pathway, but the interaction between auxin and SLs is complex.